The Poetic of Colors in Qassim Haddad’s Texts (Oh Coal, My Master: Van Gogh’s Notes) - Al-Zahrani, Amirah Ali Abdullah (Journal of Humanities & Social Sciences, 2020)
This study presents a critical approach to the poetic aspects of Qassim Haddad’s texts (Oh coal, my master) in his rewritings of Van Gogh’s life. The importance of the study lies in the new experience of the text as Qassim has provided a distinguished artistic style where he presented the biography of the Dutch artist based on the heterobiography logic. He explored the artist’s paintings which reflected his attitudes towards life and art and invested in the content of his massages. The attractiveness of this topic is the reason for conducting the study as the poet Qassim Hadadd was able to explore deeply Van Gogh’s ideas and consequently presented to us a biography of an exceedingly beautiful poetic style that presented his reading of the paintings and messages. Furthermore, texts are written in an elegant poetic language and are rich in color interpretations. The study adopts the Artistic Analytical approach that analyzed the figurative expressions of colors that have poetic connotations different from their denotative meanings which led to appreciate the aesthetic aspects of such literary texts.